2016
DOI: 10.1080/08997659.2015.1111270
|View full text |Cite
|
Sign up to set email alerts
|

Initial Detection and Molecular Characterization of Namaycush Herpesvirus (Salmonid Herpesvirus 5) in Lake Trout

Abstract: A novel herpesvirus was found by molecular methods in samples of Lake Trout Salvelinus namaycush from Lake Erie, Pennsylvania, and Lake Ontario, Keuka Lake, and Lake Otsego, New York. Based on PCR amplification and partial sequencing of polymerase, terminase, and glycoprotein genes, a number of isolates were identified as a novel virus, which we have named Namaycush herpesvirus (NamHV) salmonid herpesvirus 5 (SalHV5). Phylogenetic analyses of three NamHV genes indicated strong clustering with other members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…With data from a number of species and water bodies in Pennsylvania, New York, and Vermont, the described TaqMan and SYBR Green qPCR assays in combination were found to be sensitive, precise, and specific in detecting EEDV from wild populations of nonclinically affected Lake Trout and, in one case, hatchery Lake Trout exhibiting clinical signs and lesions associated with EEDV. From the data collected, it appears that EEDV is present in wild Lake Trout but not to the same extent as NamHV (Glenney et al 2016). To our knowledge, this work is first of its kind to present data describing the presence of EEDV in wild Lake Trout and other salmonids.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…With data from a number of species and water bodies in Pennsylvania, New York, and Vermont, the described TaqMan and SYBR Green qPCR assays in combination were found to be sensitive, precise, and specific in detecting EEDV from wild populations of nonclinically affected Lake Trout and, in one case, hatchery Lake Trout exhibiting clinical signs and lesions associated with EEDV. From the data collected, it appears that EEDV is present in wild Lake Trout but not to the same extent as NamHV (Glenney et al 2016). To our knowledge, this work is first of its kind to present data describing the presence of EEDV in wild Lake Trout and other salmonids.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, sequence analysis revealed that certain qPCR-positive isolates in the current study consistently varied by more than 5% across 307 nucleotides from the EEDV terminase gene (GenBank EU349284). These results prompted us to sequence the terminase, polymerase, and glycoprotein genes from these isolates, leading us to discover that the qPCR assay was detecting a new alloherpesvirus member in wild Lake Trout, which we named Namaycush herpesvirus (Glenney et al 2016). Thus, with the inability to culture EEDV on available FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…]; and salmonid herpesvirus‐5: namaycush herpesvirus [Glenney et al. ]) were identified and found to possess some terminase gene sequence similarity with EEDV (Glenney et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…PCR methods have been used to amplify specific partial sequences of the DNA polymerase (Hanson et al 2006), the ATPase subunit of the terminase gene (Waltzek et al 2009), and the glycoprotein gene (Glenney et al 2016). These sequences have subsequently been used to clarify phylogenetic relationships within the Alloherpesviridae family.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, this family consists of 4 genera: Batrachovirus, which includes viruses infecting frogs; Cyprinivirus, consisting of viruses that infect carp and eels; Ictalurivirus, with viruses that infect catfish and sturgeon; and lastly, Salmonivirus, representing herpesviruses that infect salmonids , ICTV 2012. However, it is noteworthy that in addition to the viruses represented by these 4 genera, members of the Alloherpesviridae family have been detected in Siberian sturgeon Acipenser baerii (Doszpoly et al 2017), walleye (Kelly et al 1983), northern pike Esox lucius (Yamamoto et al 1984), turbot Scophthalmus maximus (Hellberg et al 2002), rainbow and European smelt Osmerus mordax and O. eperlanus (Morrison et al 1996, Jakob et al 2010, pilchard Sardinops sagax neopilchardus (Crockford et al 2005), Pacific and Atlantic cod Gadus macrocephalus and G. morhua (McArn et al 1978, McCain et al 1979, Marcos-Lopez et al 2012, Atlantic salmon Salmo salar (Doszpoly et al 2013) and lake trout Salvelinus namaycush (Glenney et al 2016) that have yet to be assigned taxonomic position by the ICTV (see Hanson et al 2011 andEngelsma 2012 for overview).…”
Section: Introductionmentioning
confidence: 99%